EFEKTIVITAS PEMBELAJARAN PENDEKATAN REALISTIK TERHADAP KETERAMPILAN MATEMATIKA SISWA SLOW LEARNER Kelas V SDN SAMBUNG JAWA 3 MAKASSAR - Takdirmin; Ahmad Syamsuadi, Ahmad Syamsuadi; Qadri, Ikhbariati Kautsar; Bahar, Erni Ekafitria; Nursakia; Luthfi, Abdillah Khofial (Jurnal Riset Guru Indonesia, 2025)
This study aims to examine the effectiveness of learning models with realistic mathematical approaches to the math skills of fifth grade slow learner students at SDN Sambung Jawa 3 Makassar. This research is a quasi-experimental study with the type of research of Single Subject Research (SSR). The design used in this study is the design of A1-B-A2. The test used in this study is a written test. The technique used is using descriptive statistics and presented in the form of tables and graphs. Components used to analyze data are analysis in conditions and analysis between conditions. The results obtained in this study indicate that the learning model with a realistic mathematical approach that is applied effectively to mathematical skills in the class V slow learner students in SDN Sambung Jawa 3 Makassar. This is indicated by the percentage overlap which is 0%. Slow learner students who learn math skills (addition and subtraction) are able to understand the concepts of addition and subtraction, find solutions to the problem of the story correctly and are able to calculate correctly. The application of the learning model with a realistic mathematical approach gives progress to the mathematical skills of the slow learner students, namely students become more active and critical in solving a problem (math problem)